2018
DOI: 10.1002/dev.21784
|View full text |Cite
|
Sign up to set email alerts
|

The implications of sympathetic and parasympathetic regulatory coordination for understanding child adjustment

Abstract: The autonomic nervous system (ANS) is comprised of sympathetic and parasympathetic branches that control core adaptive systems, including cardiac regulation, across periods of rest, reactivity, and recovery. Despite their heavily intertwined functions, research examining the coordination of parasympathetic and sympathetic ANS regulation is limited. This study examined the effects of 6‐year‐olds’ (N = 198; 49.5% female; 46% Latinx) capacity for ANS reactivity and recovery in both sympathetic (i.e., pre‐ejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Kogan et al (2014) documented a negative quadratic relation between RSA activity during film clips of a person in distress and adults' self-reported prosocial behaviors such that moderate, but not extreme, levels of RSA activity during the film were positively associated with self-reported prosocial behavior, but this study did not examine reactivity in terms of the residualized change from baseline to challenge (El-Sheikh, Harger, & Whitson, 2001;Manuck, Kasprowicz, & Muldoon, 1990;Rudd & Yates, 2018). Kogan et al (2014) documented a negative quadratic relation between RSA activity during film clips of a person in distress and adults' self-reported prosocial behaviors such that moderate, but not extreme, levels of RSA activity during the film were positively associated with self-reported prosocial behavior, but this study did not examine reactivity in terms of the residualized change from baseline to challenge (El-Sheikh, Harger, & Whitson, 2001;Manuck, Kasprowicz, & Muldoon, 1990;Rudd & Yates, 2018).…”
Section: Reconciling Conflicting Evidence: a Nonlinear Hypothesismentioning
confidence: 87%
See 2 more Smart Citations
“…Kogan et al (2014) documented a negative quadratic relation between RSA activity during film clips of a person in distress and adults' self-reported prosocial behaviors such that moderate, but not extreme, levels of RSA activity during the film were positively associated with self-reported prosocial behavior, but this study did not examine reactivity in terms of the residualized change from baseline to challenge (El-Sheikh, Harger, & Whitson, 2001;Manuck, Kasprowicz, & Muldoon, 1990;Rudd & Yates, 2018). Kogan et al (2014) documented a negative quadratic relation between RSA activity during film clips of a person in distress and adults' self-reported prosocial behaviors such that moderate, but not extreme, levels of RSA activity during the film were positively associated with self-reported prosocial behavior, but this study did not examine reactivity in terms of the residualized change from baseline to challenge (El-Sheikh, Harger, & Whitson, 2001;Manuck, Kasprowicz, & Muldoon, 1990;Rudd & Yates, 2018).…”
Section: Reconciling Conflicting Evidence: a Nonlinear Hypothesismentioning
confidence: 87%
“…Although several studies have documented quadratic associations between baseline RSA and prosocial behavior, very few have examined nonlinear relations between physiological reactivity to environmental challenges and prosocial behavior. Kogan et al (2014) documented a negative quadratic relation between RSA activity during film clips of a person in distress and adults' self-reported prosocial behaviors such that moderate, but not extreme, levels of RSA activity during the film were positively associated with self-reported prosocial behavior, but this study did not examine reactivity in terms of the residualized change from baseline to challenge (El-Sheikh, Harger, & Whitson, 2001;Manuck, Kasprowicz, & Muldoon, 1990;Rudd & Yates, 2018). Likewise, a recent study showed that patterns of RSA across baseline and film conditions predicted children's helping behaviors (Miller, Nuselovici, & Hastings, 2016), but this study did not examine the magnitude of RSA response from baseline to challenge (i.e., reactivity).…”
Section: Reconciling Conflicting Evidence: a Nonlinear Hypothesismentioning
confidence: 87%
See 1 more Smart Citation
“…A few studies have examined autonomic coordination within the cardiac system using either person-oriented profile-based conceptualizations of autonomic coordination (Alkon, Boyce, Davis, & Eskenazi, 2011;Salomon, Matthews, & Allen, 2000) or interactive, continuous analytic approaches (Clark, Skowron, Giuliano, & Fisher, 2016;Rudd & Yates, 2018;Suurland, van der Heijden, Huijbregts, Van Goozen, & Swaab, 2017). These studies have revealed interesting developmental patterns (e.g., coordinated profiles of regulatory activity appear to increase across the first five years of life; Alkon et al, 2011Alkon et al, , 2014 and adaptive implications of autonomic coordination (e.g., children who had interactive patterns of sympathetic and parasympathetic coactivation or coinhibition in response to interpersonal stress as infants show higher levels of physical aggression than those who evidenced reciprocal autonomic coordination; Suurland et al, 2017).…”
Section: Studies Of Autonomic Coordinationmentioning
confidence: 99%
“…Although extensive evidence confirms the ability of each branch of the autonomic nervous system to act independently (Berntson, Cacioppo, & Quigley, ; Berntson, Cacioppo, Quigley, & Fabro, ), the extent and nature of coordination between sympathetic and parasympathetic branches may have additional meaning beyond the amount of activation in either branch alone (Quas et al, ; Rudd & Yates, ). The extent of coordination between sympathetic and parasympathetic influences on cardiac function is presumably regulated by higher‐order central nervous system networks capable of integrating complex information related to situational context and motivational goals to deliver efferent signals to the peripheral nervous system in support of the behavioral responses necessary to meet the current environmental demands (e.g., Critchley et al, ; Smith, Thayer, Khalsa, & Lane, ).…”
Section: Introductionmentioning
confidence: 99%